2021
DOI: 10.1002/dta.3116
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pharmaceuticals in “dirty sprite” using gas chromatography and mass spectrometry

Abstract: Dirty Sprite, also known as “lean” or “purple drank”, is a preparation associated with the presence of codeine and promethazine. These drinks, predominantly used by young people, are mixtures of, for example, soft drinks, prescription medicines, and prescription cough syrups. The use of these illicit preparations started in Texas in the 1960s and become popularized in the 1990s. However, the misuse of these cocktails has become more common in other countries to date, for example, in Thailand. Given the illicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The extraction efficiency of the developed method (85.0–94.9%) is in a similar range or better than that of the other methods. The limit of detection was either comparable to that reported by Juhascik et al , 28 Hamid et al 27 and Rosenberger et al 33 or better than that reported by Njuguna et al 26 and Nishikawa et al 30 from previous reports. Additionally, the extensive linear range for each analyte indicates the feasibility of analyzing lean cocktail samples.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…The extraction efficiency of the developed method (85.0–94.9%) is in a similar range or better than that of the other methods. The limit of detection was either comparable to that reported by Juhascik et al , 28 Hamid et al 27 and Rosenberger et al 33 or better than that reported by Njuguna et al 26 and Nishikawa et al 30 from previous reports. Additionally, the extensive linear range for each analyte indicates the feasibility of analyzing lean cocktail samples.…”
Section: Resultssupporting
confidence: 74%
“…26 In addition, the proposed extraction method used a small volume of organic solvent which is also less than those of other reports. 26,28,29 The total extraction time of our method was 35 min, which is longer than that required in liquid-liquid extraction (LLE) and headspace-solid phase microextraction (HS-SPME) as reported by Njuguna et al, 26 Nishikawa et al 30 and Rosenberger et al 33 However, an emulsion is obtained by the liquid-liquid extraction (LLE) method. The extraction time of the proposed SBSE method is faster than PDMS coated SBSE as reported by Crifasi et al 31 The extraction time of our method (35 min) was nonetheless sufficient to simultaneously extract all the analytes of interest.…”
Section: Comparison With Other Methodsmentioning
confidence: 75%
See 2 more Smart Citations
“…These so‐called “dirty sprite” drinks are offered for sale and labeled to contain pharmaceutical substances promethazine and codeine. Interestingly, the authors report detections of cocaine, codeine promethazine, and dihydrocodeine 20 …”
Section: Medicines and Active Pharmaceutical Ingredientsmentioning
confidence: 99%